Erratum to: Learning-Outcomes Factors of Circular Business Model-Training for Waste-Bank Managers - JABM Editorial (School of Business, Bogor Agricultural University (SB-IPB), 2026)
Correction to: Hidayati, A., Widjaja, A., Kountur, R., & Phangestu, J. (2025). Learning-Outcomes Factors of Circular Business Model-Training for Waste-Bank Managers. Jurnal Aplikasi Bisnis dan Manajemen (JABM), 11(3), 759–759. https://doi.org/10.17358/jabm.11.3.759 An error appeared in the article entitled “Learning-Outcomes Factors of Circular Business Model-Training for Waste-Bank Managers” published in Jurnal Aplikasi Bisnis dan Manajemen (JABM). In the published article, an error was found in the reference list, where one citation used in the manuscript was not included in the reference list. The correction for the error is as follows: Correction on the reference list: Missing reference:Laing, I.F. (2021). The Impact of Training and Development on Worker Performance and Productivity in Public Sector Organizations: A Case Study of Ghana Ports and Harbours Authority. International Research Journal of Business and Strategic Management, 2, 438–449. Should be added to the reference list. This correction is necessary to ensure the completeness of citations, maintain academic integrity, and align with ethical standards of scientific writing. The original article can be access online at:https://doi.org/10.17358/jabm.11.3.759